Clinical performance of the pseudo-non diffracting beam Toric EDOF intraocular lens: visual function, rotational stability, and quality of life - Bonacci, Erika; Anastasi, Marco; Pagnacco, Camilla; Barzaghi, Francesca; Serraiotto, Arianna; Pilati, Francesca; Fasolo, Adriano; Pedrotti, Emilio (Frontiers in Medicine, 2025)
PurposeTo evaluate visual acuity, refractive outcomes, rotational stability, and patient-reported satisfaction 3 months after bilateral implantation of the Lucidis Toric extended-depth-of-focus (EDOF) intraocular lens in cataract patients with 1.00–3.00 D of regular corneal astigmatism.MethodsProspective, single-arm study of 25 patients (50 eyes) undergoing phacoemulsification with bilateral Lucidis Toric IOL implantation. The primary endpoint was binocular uncorrected distance visual acuity (UDVA) at 3 months. Secondary endpoints included monocular/binocular UDVA, distance-corrected VA (DCVA) at 4 m; intermediate (80 cm, 66 cm) and near (40 cm) uncorrected and distance-corrected acuities; defocus curve; residual spherical equivalent (SE) and cylinder; IOL rotation; optical quality (MTF cutoff, Strehl ratio, HOA RMS); contrast sensitivity; halometry; and NEI-RQL-42. Paired t-tests or Mann–Whitney tests compared pre-/postoperative values.ResultsAt 3 months, the mean postoperative spherical equivalent was 0.17 ± 0.52 D (median 0.00 D; range −0.75 to +0.75 D) and the mean refractive cylinder was 0.04 ± 0.32 D (median 0.00 D; range −0.50 to +0.50 D). Median IOL rotation was 2.1 ± 2.3 degrees, with no eyes requiring repositioning. Mean binocular UDVA, UI80VA, UI66VA and UNVA were −0.01 ± 0.1, 0.08 ± 0.24, 0.04 ± 0.1, and 0.01 ± 0.14 logMAR, respectively. There were no statistically significant differences between uncorrected and distance-corrected visual acuities at any distance. The binocular defocus curve showed visual acuity better than 0.1 logMAR from +0.50 D to −3.00 D. NEI-RQL-42 scores indicated high patient satisfaction, particularly in clarity of vision, far, near vision, activity limitations, and glare domains.ConclusionBilateral Lucidis Toric EDOF IOL implantation delivers stable rotational performance, broad-range uncorrected vision, and high spectacle independence in astigmatic cataract patients. Future randomised, head-to-head trials with longer follow-up are warranted.